1989
DOI: 10.1111/pace.1989.12.p1.16
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Rate Responsive Atrial Pacing in Patients with Sick Sinus Syndrome

Abstract: We studied heart rate response and blood lactate changes during treadmill exercise testing in 10 patients with sick sinus syndrome (SSS) and normal atrioventricular (AV) conduction in whom an activity detecting multi‐programmable rate responsive pacemaker was implanted for atrial pacing (AAI pacing). Treadmill exercise testing was performed twice in each patient under the two different AAI pacing modes: rate responsive function off (fixed rate 60 pulses per minute [ppm]; RR‐off) and rate responsive function on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…A previous report showed that dual-chamber pacing may also prevent the progression to AF by overdriving the atria, which is somewhat effective in suppressing atrial ectopic activity and AF 10. However, Nielsen, et al showed that a long-term dual-chamber pacing induces left atrial dilation by right ventricular (RV) pacing, subsequently promoting AF, and Kristensen, et al demonstrated that single atrial chamber pacing was associated with significantly less AF in patients with SSS and normal AV conduction 11.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report showed that dual-chamber pacing may also prevent the progression to AF by overdriving the atria, which is somewhat effective in suppressing atrial ectopic activity and AF 10. However, Nielsen, et al showed that a long-term dual-chamber pacing induces left atrial dilation by right ventricular (RV) pacing, subsequently promoting AF, and Kristensen, et al demonstrated that single atrial chamber pacing was associated with significantly less AF in patients with SSS and normal AV conduction 11.…”
Section: Discussionmentioning
confidence: 99%
“…These patients also tend to exhibit more severe peripheral and coronary arterial disease 14 . Recent evidence suggests, however, that atrial pacing in AAI and AAIR modes reduces morbidity and mortality by decreasing the incidence of atrial fibrillation and peripheral embolisation as well as improving congestive cardiac failure compared to ventricular pacing 15 , 16 …”
Section: What Are the Indications For Permanent Cardiac Pacing?mentioning
confidence: 99%
“…These modes utilise the normal conduction system and are the most ‘physiological’ presently available 29 . Atrial pacing also improves long‐term survival and tends to decrease the incidence of paroxysmal atrial tachyarrhythmias compared to ventricular pacing modes 15 , 16 . Clearly, AV nodal conduction must be closely assessed and proven to be normal prior to, or during, the implantation procedure.…”
Section: Which Pacing Mode?mentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen male and 17 female patients, mean (SD) age 65 (12) years, satisfied the inclusion and exclusion criteria and were admitted for implantation of programmable AAIR systems. '5 Medtronic Activitrax II and Telectronic Meta MV generators with their recommended atrial leads, were implanted alternately.…”
mentioning
confidence: 99%